Gambaran Pengetahuan Tentang Perilaku Perawatan Diri pada Pasien Gagal Jantung - Marbun, Agnes Putri S; Tarigan, Mula; Sitohang, Nur Asnah (Journal of Telenursing (JOTING), 2024)
This study aims to determine the description of knowledge about self-care behavior in heart failure patients. The research method used is quantitative research with a descriptive approach. Sampling was taken using a purposive sampling technique with a total sample of 50 people with heart failure who were hospitalized. Data collection used the Dutch Heart Failure Knowledge Scale instrument. Data were analyzed using univariate analysis tests with presentation of tables in the form of frequency distributions and percentages. The results showed that knowledge about self-care behavior in hospitalized heart failure patients tended to vary, with an average knowledge score of 4.44 and a standard deviation of 1.554. In conclusion, although there are variations in patient knowledge, nurses have an important role in improving patient knowledge and care, both during hospital treatment and after the patient goes home. This is important to help patients optimize their function in carrying out daily activities. Keywords: Heart Failure, Knowledge, Self-Care Behavior.